Variation of adult admission and co-morbidity to general intensive care unit of BSMMU: Impact on outcome - Faruque, Labib Imran; Huda, Qumrul; Banik, Debasish; Rahman, AKM Shafiqur (University Heart Journal, 2009)
A retrospective study was done in ICU of BSMMU during January to June 2007 with a total number of 157 patients. Patients were included from this hospital and also from private hospitals. In accordance of the criteria for analysis a structured questionnaire was used whereas data obtain from hospital record sheets and file. We observed admission diagnosis, co-morbidities, length of stay, different procedures and overall outcome. Among 157 Patients age group of 61-70 yrs. constitutes the major proportion, which was 20.4% and male was 61.8%. 108 patients (75.2%) were admitted due medical illness and among which respiratory failure was 15.3%, intracranial hemorrhage was 13.4%.Among 112 deaths 77 died after 96 hours of admission. Death occurred in 90.5% for non-traumatic hemorrhage and 94.1% cases for pneumonia (P < 0.5). We did not find any significant association between outcome and co-morbidities except for cerebrovascular in sufficiency (P < 0.5). Therefore we can predict that admission diagnosis and other factors. doi:10.3329/uhj.v4i2.2070 University Heart Journal Vol. 4 No. 2 July 2008 p28-31